Coletivos e participação política no Brasil: reflexões para a compreensão de novas lideranças - Pitondo, Jimmy Augusto Moreira (2017)
This research aims to investigate the emergence of urban collectives as new forms of political participation in Brazil. Refusing institutional means available, they are supported by a type of political representation that does not require the authorization of the represented, where there is no specific monopoly or territoriality, but only affinity. The initial hypothesis of the work is that despite the existence of mechanisms characteristic of the democratic regime that foster direct or indirect political participation and institutions responsible for the transparency of public actions through accountability, there is a negative perception of the Citizens about the efficiency of this group, making the innovations in the field of political participation a reactive and symptomatic phenomenon. The work is a bibliographic study and therefore was carried out with qualitative methods through various authors of political science and sociology. It begins with the investigation of a type of leadership characteristic of these collectives, here called Horizontal, to analyze the Democratic regime and its theoretical and practical implications, making it possible to launch a safe look at the process of redemocratization in Brazil and to confer correspondence between Principles that underlie the Constitution of 1988 and its effective application in terms of political participation and mechanisms of inspection and control, important for understanding the contemporary scenario. Finally, some groups were selected to test the hypothesis in practice, highlighting the formation of more active, critical and politicized groups that not only claim actions of the public institutions, but act on their own in solving problems that do not trust the State for Not to believe in their efficiency, showing signs of dissatisfaction not with Democracy itself, but with governments and institutionalized forms of representation. In this sense, the dissertation is inserted in the field of Social Sciences, focused on the study of political institutions and collective action, seeking to expand the field of analysis with new perspectives